PENGETAHUAN, SIKAP DAN PENDIDIKAN IBU DENGAN KEJADIAN ISPA PADA BALITA DI PUSKESMAS 7 ULU KOTA PALEMBANG - Arly Febrianti (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2020)
ISPA is the upper respiratory tract disease with particular attention to lung inflammation(pneumonia) and not the ear and throat diseases.The purpose of this study is to determine the relationship of knowledge, attitudes and maternaleducation with incidence of respiratory infection in infants in the region of Palembang CityHealth Center 7 Ulu 2019. This type of quantitative research is conducted using survey methodsof analytic cross sectional approach. The number of samples of this study of 30 respondents.From the results of bivariate analysis, no significant association between maternal knowledge ofthe incidence of ARI in infants (p value 0.013), no significant relationship between maternalattitude to the incidence of ARI in infants (p value 0.002), no significant association between theincidence of maternal education ARI in infants (p value 0.004). Expected for the mother, may be active to follow any counseling provided by health workers as well as asking about the material that has not been understood in the hope of changing unhealthybehaviors. As a child away from direct exposure of patients with ARI, always keeping the houseclean.